Effectiveness of Group Guidance on Growth Mindset for Improving Students' Effort Regulation - Fitri Windi Astuti; Sunawan; Heru Mugiarso (Jurnal Bimbingan Konseling, 2024)
The issue of effort regulation among students has negative implications for academic conditions such as declining achievement, anxiety, and stress, necessitating intervention strategies to strengthen effort regulation. Therefore, this study aimed to enhance effort regulation through a growth mindset intervention using an experimental design.  Purposive sampling was employed to select 20 students exhibiting low levels of effort regulation.  Data collection utilized scales for a growth mindset and effort regulation.  The results indicate the effectiveness of group guidance on growth mindset for improving effort regulation in the experimental group compared to the control group.  Measurement (time) has an observed effect on enhancing effort regulation.  This study clarifies the effectiveness of group guidance on a growth mindset for enhancing effort regulation.